DAMPAK PENDIDIKAN AGAMA ISLAM TERHADAP PERUBAHAN PERILAKU ANAK DIDIK PEMASYARAKATAN (ANDIKPAS) - Helianto Suryadi (Al-Muaddib : Jurnal Ilmu-Ilmu Sosial & Keislaman, 2020)
As stated in Law number 11 of 2012 concerning the Juvenile Justice System, that Lapas fostered children are entitled to education and training while staying in correctional institutions. Islamic Religious Education Learning in Lapas Anak has differences with learning PAI in formal institutions. In formal schools learning emphasizes more on the academic ability of students while learning in Lapas Anak more emphasizes on moral material this is because the background of students in Lapas who need moral material to improve the morals of students. So the learning of Islamic Education in Lapas Anak is more flexible, as the substance of formal education in order to support lifelong education. The impact of Islamic Religious Education on changes in correctional behavior (andikpas) among others can be seen from the speech patterns and the language used by Lapas students is already good, especially facing older people. In terms of worship to Allah there is also progress, especially the prayer activities in congregation. Fluency in reading the Koran is also much improved with the provision of recitation materials.